Upaya Peningkatan Hasil Belajar IPS Melalui Metode Demontrasi Dengan Materi Lingkungan Kabupaten/Kota Di Kelas IV SDN 014 Terusan Tahun Pelajaran 2021-2022 - Thamrin, Husni (Faculty Of Education, 2024)
When the social studies learning process takes place, the learning outcomes obtained by students are very low, because the teacher still applies conventional learning, resulting in students appearing passive in the learning process. One method that is able to encourage students to play an active role during the learning process, so that it can improve student learning outcomes is the Demonstration method. This classroom action research (PTK) was carried out in class IV (four) of SDN 014 Kanan with a total of 10 students, 3 male students and 7 female students. This research was carried out through the planning, implementation, observation and reflection stages. The data collection process was carried out through analyzing student learning outcomes and analyzing observation sheets for students and teachers. Meanwhile, the research results show an increase in the absorption capacity and activities of teachers and students. In cycle 1 activities, student learning outcomes were obtained at 62.4. It increased to 84.0 in cycle II. While classical completeness in cycle I was 36%, it increased to 90% in cycle II. Thus, efforts to apply the Demonstration Method succeeded in improving learning outcomes, student and teacher activities as well as increasing student interest and motivation to learn.